The Relationship between Body Image and Psychological Stress Levels in Patients at the Dermatology Clinic of Sultan Agung Islamic Hospital - Nur Afifah; Betie Febriana (Health and Technology Journal (HTechJ), 2025)
Body image and psychological stress influence patient well-being in the dermatology clinic. This study analyzes the relationship between body image and psychological stress levels in patients at the Dermatology Clinic of Sultan Agung Islamic Hospital. The study used a cross-sectional design with 100 respondents selected through a total sampling technique. The research instruments were the Multidimensional Body-Self Relations Questionnaire (MBSRQ) subscale questionnaire to measure body image and the Perceived Stress Scale (PSS) to measure psychological stress. Data analysis used the Pearson correlation test. The results showed that most respondents had a positive body image (55%) and moderate psychological stress (82%). The Pearson test produced a p-value of 0.008 with a correlation coefficient of 0.266, indicating a significant positive relationship. This study concludes that positive body image is associated with lower levels of psychological stress. A holistic approach is needed in dermatological services that encompasses patients' physical and psychological aspects.